Sustainable Development Planning of Surabaya City: Pursuing Inclusive and Sustainable Growth - Suyanto, Suyanto; Krisprimandoyo, Denpharanto Agung; Jusnita, R. Ayu Erni; Bernardus, Denny; Riyadi, Slamet (Journal of Business Management and Economic Development, 2024)
This research investigates sustainable development planning in Surabaya City with a qualitative approach. This study aims to identify factors that influence inclusive and sustainable growth in the context of complex economic and business dynamics. This research uses policy analysis and comprehensive case studies to dissect challenges and opportunities that become obstacles or promising paths for Surabaya City in achieving sustainable development goals. The findings of this study illustrate the picture of the urban development landscape. The findings emphasize the need for improved policies that encourage and actively support community participation, thus creating a supportive environment for realizing social and economic inclusivity. In addition, the study highlights the importance of targeted interventions in the form of poverty alleviation programs, which, combined with strategic empowerment initiatives aimed at micro, small, and medium enterprises (MSMEs), prove to be very important instruments in generating sustainable economic growth. Keyword: community participation, development planning, MSME Empowerment, policy analysis, sustainable development goals